Enhancing disaster risk reduction through adoption of climate smart initiatives in marginal communities of southern Zimbabwe - Makuvaro Veronica; Defe Rameck; Matsa Makomborero Mark; Mapfungautsi Rungano; Muchianga Nyasha (Elsevier, 2022)
Climate change and variability are exacerbating communities’ vulnerability and exposure to climate induced disasters and risks. The paper examines the contribution of climate smart initiatives in enhancing disaster risk reduction in vulnerable and exposed communities of Chiredzi District. The research adopted a mixed research design of both qualitative and quantitative methods where questionnaires, interviews and observations were used. Questionnaire administration was done to randomly selected households using the Kobo collect software. Inter views were conducted with purposively selected key informants from CARE, PLAN international, the Department of Agricultural Technical and Extension Services (AGRITEX), The Veterinary Services Department, Rural District Council and the District Development Co-ordinator’s office. Findings revealed that climate change manifested through increased occurrence of hazards such as floods, drought and dry spells which were significantly compromising food security status that is availability, utilisation and access to the communities of Chiredzi District. Several climate smart initiatives were being implemented in the study area to reduce the impacts of climate-induced risks on the major livelihood sources, crop and livestock production as well as those that directly threatened human lives. Adoption of climate smart initiatives was significantly contributing to strengthening of community capacities to withstand climate induced risks and disasters. Development actors and government must increase the number of beneficiary wards and design more initiatives so as to increase communities’ capacities to withstand future shocks as climate change is projected to continue to change in the next decades.